Determinants of Internet Financial Reporting : An Empirical Investigation on UAE Public Listed Companies - Al-Mansour, Ammar Yaser Mansour (2009)
The main purpose of this study is to provide insights into the use of Internet for disseminating financial information among UAE publicly listed companies and to put some lights on the factors that affect such companies in adopting financial disclosure through internet. The findings show that UAE companies are still to some extent placed behind those in other developed countries and even with other developing countries. This study additionally examined the effect of three factors namely firm size, leverage and profitability on internet financial reporting (IFR). A linear regression analysis is applied for this purpose. Findings reveal that profitability and leverage do not significantly influenced internet financial reporting. The result also shows that there is a significant positive linkage between the amount of financial disclosure through internet and size of companies.